"Aquabin" / NurFithriyaani Kamil...[et al.] - Kamil, NurFithriyaani (2018)
By now, report shows that our oceans are turning into swirling garbage dumps. It is estimated that some 8 million metric tons of plastic waste enter global waters every year. This Aquabin is made to reduce water pollution that caused by human such as trash dumping, food waste, and eutrophication problem. Water pollution is also a threat to aquatic life, so it is also made to save the aquatic life. Cleaning up the ocean or beach manually is time and labor consuming. So, with Aquabin, massive human intervene is not required anymore. This Aquabin develops innovative upstream solutions for cleaner and more sustainable marinas. It is made to reduce water pollution that caused by human such as trash dumping, food waste, and eutrophication problem. The Aquabin is a floating rubbish bin that is located in the water at marinas, docks, rivers, lakes, public waterways and oceans. The Aquabin is a unique and sustainable water system cleaning technology. It is an automated rubbish bin that catches everything from plastic bottle, paper, oil, fuels and detergent which built from recycled material. Water is sucked in from the surface and passes through a filter fibers bag inside the Aquabin. With the aid of impeller, the water is then remove back into the ocean leaving litter and debris trapped in the filter fibers bag to be disposed of properly. So, with Aquabin, massive human intervene is not required anymore.